A voice from the South - Cooper, Anna Julia (University of North Carolina at Chapel Hill Library, 2017)
The first book by Anna J. Cooper, A Voice From the South, presents strong ideals supporting racial and gender equality as well as economic progress. It’s a forward-thinking narrative that highlights many disparities hindering the African American community. Anna J. Cooper was an accomplished educator who used her influence to encourage and elevate African Americans. With A Voice From the South, she delivers a poignant analysis of the country’s affairs as they relate to Black people, specifically Black women. She stresses the importance of education, which she sees as a great equalizer. Cooper considers it a necessary investment in not only the individual but the community. She also criticizes the depictions of African Americans in literature by some of the day’s most popular authors. She calls for more realistic portrayals that are both honest yet positive. Cooper provides an unflinching critique of mainstream America as it relates to the Black population. A Voice From the South broaches pivotal topics such as women’s rights, segregation and the need for higher education. With an eye-catching new cover, and professionally typeset manuscript, this edition of A Voice From the South is both modern and readable.
Première publication 1892 https://docsouth.unc.edu/church/cooper/cooper.html
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; capitalisme; droits des femmes*; féminismes noirs; histoire et politique; militance; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; éducation; états-unis

Blanches et Noires : histoire(s) des Américaines au XIXe siècle - Lehuu, Isabelle (Institut de recherches et d'études féministes, 2011)
«Les chapitres qui suivent mettent en lumière tant la parole des femmes que le discours sur les femmes, les actions et les représentations. Ils explorent la réalité quotidienne de femmes ordinaires du XIXe, jeunes et moins jeunes, mariées et célibataires, blanches et noires, au Nord comme au Sud, qui sont restées silencieuses, souvent dans l’ombre d’un mari, d’un père ou d’un maître. Leurs témoignages, les mots qu’elles ont laissés dans les sources publiques et privées, les gestes qu’elles ont posés aussi bien dans le cadre de leurs relations affectives qu’au sein de leur exploitation familiale, leur réseau social, leur travail, leur église, leur communauté urbaine ou villageoise, leur région, sont autant d’indices à décoder pour dresser un portrait nuancé et documenter la condition des femmes aux États-Unis dans toute sa diversité sociale et culturelle.»
https://revues.uqam.ca/prefix/cahiers-iref/agora-no-2-2012blanches-et-noires-histoires-des-americaines-au-xixe-siecle/
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; black feminism; cours; discipline; esclavagisme; femmes* blanches; femmes* noires; féminisme afroaméricain; féminismes noirs; his4443; histoire; histoire des femmes*; intersectionnalité; justice sociale; militance; mouvement aboitionnisme; philosophie politique; premier cycle; privilèges; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; états-unis (sud); études féministes